Accompaniment of The Entrepreneurial Group of Non-MSG Snakehead Fish Crackers Sumber Rezeki Banjarmasin - Lena Rosida; Oski Illiandri; Siti Kaidah; Juhairina Juhairina; Muhammad Bari NurQaedi; Kanessha Winola Sunata (Jurnal Berkala Kesehatan, 2022)
Cork fish (Channa sp) is one of the freshwater fish that is useful for maintaining health and can be made in the form of fish crackers. One of the micro-business groups that make cork fish crackers is the Sumber Rezeki Banjarmasin Entrepreneurial Group. This entrepreneurial group developed the manufacture of non-Monosodium Glutamate (MSG) cork fish crackers. Based on the results of an interview with the head of the Sumber Rezeki Banjarmasin Entrepreneurial group, information was obtained that the North Kuin community's interest in these non-MSG crackers was still low because the crackers without MSG were less delicious than those containing MSG. The existence of this opinion can cause their enthusiasm and commitment to maintain products without MSG will decrease and it can even cause them to follow other cracker products that use MSG. Therefore, the Community Serviceteam provided a solution in the form of strengthening commitment and counseling about the dangers of using excessive MSG and the importance of fish consumption for health. This Community Service activity is carried out in 2 ways, namely psychological assistance and health education. Psychological assistance through focus group discussions (FGD) can increase the number of participants who believe they want to continue the non-MSG cracker business from 50% to 90%.